Predicting success factors in financial accounting courses for Diploma in Accountancy programme (northern region UiTM) / Wan Faizah Wan Abdullah…[et al.] - Wan Abdullah, Wan Faizah; Abdul Rahim, Noraini; Marzuki, Marzlin; Abu Bakar, Siti Salmah; Wan Salleh, Wan Zulkipli (Research Management Institute, 2004)
The main objective of this study is to investigate the factors that contribute to the success in the performances of Financial Accounting I, 2, 3 and 4 of Diploma in Accountancy Programme at Universiti Teknologi MARA Northern Campuses (Kedah, Perils and Perak) All the data were obtained from the Student Affairs Department at each respective campus, t-test. Pearson Correlation and Stepwise Multiple Regression are used to anal\/e the data Findings show that the performance of students with SPM Accounting and SPM Additional Mathematics are higher for all Financial Accounting courses, the results also show that SPM Accounting, SPM Additional Mathematics and SPM English are the best predictors for Financial Accounting 1. For other Financial Accounting courses, the immediate prior accounting determines the performance of each course.